2020
DOI: 10.2169/internalmedicine.3803-19
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Depression with Type D Personality and Coping Strategies in Patients with Coronary Artery Disease

Abstract: Objective Depression in patients with coronary artery disease (CAD) has been a risk factor for adverse cardiovascular events. However, personality types, strategies for coping with stressors, and their associations with depression have not been fully elucidated in patients with CAD. This study explored depression in patients with CAD and examined its association with personality types and coping strategies. Methods A prospective observational study of 89 patients with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
(54 reference statements)
1
8
0
1
Order By: Relevance
“…Type D personality had an indirect effect through negative correlation with self-management and cognitive illness perception; an indirect effect on approach coping through negative correlation; and a direct effect on depression through positive correlation. This result aligned with previous ndings in which the type D personality negatively correlated with cognitive illness perception and health behaviors in patients with coronary artery diseases [40], and with other studies where it had an impact on depression through positive correlation [22,42]. These effects may be attributed to the fact that individuals with a type D personality show far greater negative emotions toward experiencing diseases or symptoms than others, while simultaneously facing di culties with potentially bene cial social interactions [22].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Type D personality had an indirect effect through negative correlation with self-management and cognitive illness perception; an indirect effect on approach coping through negative correlation; and a direct effect on depression through positive correlation. This result aligned with previous ndings in which the type D personality negatively correlated with cognitive illness perception and health behaviors in patients with coronary artery diseases [40], and with other studies where it had an impact on depression through positive correlation [22,42]. These effects may be attributed to the fact that individuals with a type D personality show far greater negative emotions toward experiencing diseases or symptoms than others, while simultaneously facing di culties with potentially bene cial social interactions [22].…”
Section: Discussionsupporting
confidence: 91%
“…However, participants' scores for approach coping were relatively low, ranging from 0 to 3, with a mean score of 1.40. This may be due to high percentages of participants with type D personalities (56.8%) and depression (54%), both of which have been found to correlate with low levels of approach coping such as planning [42]. In the case of multimorbidity patients, coping mechanisms such as denial and avoidance has been most frequently observed [44].…”
Section: Discussionmentioning
confidence: 99%
“…There are no answers to these questions yet. It has been suggested that the development of adequate coping strategies in individuals with type D personality would help preventing the development of depressive reactions [13]. Apparently, the reluctance of people with type D personality to seek help (fear of social interactions) complicates the establishment of full-fledged contact between the psychotherapist and the patient, which is a necessary condition for an effective work with psychosomatic diseases [21].…”
Section: Discussionmentioning
confidence: 99%
“…Since coping strategies are a stabilizing factor, due to which the psychosocial adaptation of an individual is maintained during the period of exposure to stress, and they can be considered as a potential target for behavioral interventions [11]. This explains the recent interest in the study of coping strategies in people with type D personality [12][13][14]. However, such publications are scarce, and the studies were carried out in foreign countries differing from Russia in their cultural, economic and linguistic environment.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis may have explained the role of depression on the prediction of CHD on healthy populations, but the relationship between vital exhaustion and depression is yet to be ascertained. On the other hand, patients with type-D personality are more likely to develop depression after an acute coronary event due to their lack of planning and coping strategies [ 38 ].…”
Section: Discussionmentioning
confidence: 99%